Transforming Quality Management with Industry 4.0 Technologies: A Meta-Analytic Review of AI, Blockchain, IoT, and Big Data - SOUAD LAHMINE; FATIMA BENNOUNA (International Journal of Industrial Engineering and Production Research)
Quality 4.0 is the fusion between the long-standing quality management tenets and Industry 4.0 technologies like AI, Blockchain, IoT, and Big Data. Although it can improve product quality, control operational efficiency, and supply chain transparency for organizations, adopting these technologies comes with high challenges. This study, therefore, carries out a meta-analytic review incorporating 80 peer-reviewed papers from between 2018 to 2024 to exposit the effectiveness, challenges, and prospects of Quality 4.0. Results show that machine learning-based predictive analytics significantly reduce defect rates and production costs, while Blockchain enhances visibility into the supply chain. On the other hand, organizational readiness and workforce training are major barriers. The paper can give much-needed input to practitioners through actionable recommendations and suggest avenues for further research that would advance Quality 4.0 adoption.